Reanalysis of 500 hP patterns generating temperatures above 50 ° C in West Asia - Hadi Zerafati; Yousef Ghavidel; Manuchehr Farajzadeh (تحقیقات کاربردی علوم جغرافیایی)
In this study, for statistical studies to determine days whit temperature above 50°c, the reanalyzed data of the nineteenth, twentieth and twenty-first centuries for the West Asia region (12 to 42.5 degrees north latitude and 36 to 63.5 degrees east longitude) have been used. Also, for synoptic analysis of extreme temperatures, HGT, AIR, UWND, VWND and SLP data were used. To conduct this research, first, extreme temperature data above 50° during the last 185 years were extracted for the study area in the hot season (June, July, August and September). After identifying days whit above 50° c, HGT data at the level of 500 hp were extracted and WARD clustering was applied. Finally, after identifying the clusters, the days whit the highest temperature that occurred in each cluster were selected for synoptic analysis. It can be said that all altitude patterns of geopotential meters (HGT) at the level of 500 hp show that the main cause of occurrence and distribution of temperatures above 50°c in West Asia are high-altitude (high-pressure) subtropical West Asia, which due to the location of its high-pressure core on the Zagros and sometimes the Arabian Peninsula, it has been referred to as the Zagros or Saudi high-pressure in terms of interest and taste. What is certain, however, is the high-pressure independent identity of the subtropical Azores, which has been mentioned in numerous articles and is known to be the main cause of the heat in the West Asian region, especially Iran.